Analisis Kelayakan Finansial dan Keberlanjutanusaha Ternak Kambing Kampung Notoharjo Kecamata Trimurjo Kabupaten Lampung Tengah Provinsi Lampung - Lestari, Oktavia; Zulkarnain, Zulkarnain (Penerbit Goodwood, 2024)
Purpose: The aim of this research is to analyze the financial feasibility of goat farming in Notoharjo Village, Central Lampung Regency, Lampung Province Method: The research was conducted in Notoharjo Village, Trimurjo District, Central Lampung Regency, Lampung Province with a sample size of 30 goat breeders from 90 populations formulated using the Slovin formula. The sampling method uses Purposive Sampling and the analytical method used in the research is Financial Feasibility Analysis with the investment criteria Net Present Value (NPV), Net Benefit Cost Ratio (Net B/C), Gross Benefit Cost Ratio (Gross B/C), Internal Rate of Return (IRR), and Payback Period (PP). Results: The results of the financial analysis show an NPV value of IDR 37,552,311.47, Net B/C 6.09, Gross B/C 2.79, IRR 45% and PP 3 years 5 months. Conclusions: The conclusion obtained is that goat farming is profitable and financially feasible to continue (based on NPV, Net B/C, Gross B/C, IRR, and PP). The sustainability analysis also indicates that goat farming is running well and is viable for further development. Limitations: The business that is financially measured is in the form of goat livestock carrying out rearing activities that are ready to be sold Contribution: The goat farming business that is being run is profitable and sustainable so that farmers who want to start a goat farming business can consider the feasibility analysis that has been analyzed which is used as a reference for beginner farmers.